Lives on the Line: The Online Lives of Girls and Women With and Without a Lifetime Eating Disorder Diagnosis - Bachner-Melman, Rachel; Zontag-Oren, Einat; Zohar, Ada H.; Sher, Helene (Frontiers in Psychology, 2018)
This study aimed to compare the scope, internet use patterns, and degree of online need satisfaction of girls and women with and without a lifetime eating disorder (ED) diagnosis. Participants were 122 females aged 12-30, 53 with a lifetime ED diagnosis recruited via a hospital-based treatment program, and 69 age-matched controls recruited via normative social media sites. Participants completed questionnaires assessing disordered eating, body image, positive and negative affect, general distress, and life satisfaction, and completed an online survey about the scope of their internet use, the frequency of watching and posting pictures and videos, online friendships and social comparison, fulfillment of needs online, and mood after internet use. All questionnaire scores differed significantly between groups in the expected directions. Whereas overall, ED and control groups spent similar amounts of time online (6.21, SD=5.13), they spent this time differently. ED participants reported devoting 56.7% of their online time to eating, weight and body image, versus 29.1% for controls, and spent significantly more time than controls on forums and blogs (t=-5.3, p<0.0001, Cohen’s d=0.87). They also engaged more often in social comparison (t=3.6, p<0.005, Cohen’s d = 0.65), had a higher online-offline friend ratio (t=3.7, p<0.0001, Cohen’s d=0.65), and more online friends with ED (t=5.4, p<0.0001, Cohen’s d=0.89). In comparison to controls, ED participants reported that their use of forums and blogs gave them more eating- and weight-related advice, and a greater sense of belonging, social support, and safety resulting from anonymity, with effect sizes of 0.63-0.96. However, they also reported more negative affect after posting online. Most online behaviors and patterns correlated positively with measures of symptomatology and negatively with measures of psychological health, in both groups. Internet use was rarely addressed in therapy. Professionals, families and friends should help people with disordered eating and EDs to broaden the scope of their internet use. They should invest less in food- and weight-related forums/blogs, expand their “real life” social lives and develop their interpersonal skills, so that their legitimate needs can be satisfied face-to-face, rather than virtually. Clinicians should address the online lives of their ED clients in therapy.